A Raman-Based Investigation of the Fate of Li2MnO3 in Lithium- and Manganese-Rich Cathode Materials for Lithium Ion Batteries. Issue 7 (14th April 2015) - Wu, Qingliu; Maroni, Victor A.; Gosztola, David J.; Miller, Dean J.; Dees, Dennis W.; Lu, Wenquan
Abstract : The relationship between structure and electrochemical performance of lithium- and manganese-rich cathode materials with the general formula xLi2 MnO3 (1-x)LiMO2 is under intensive study world-wide in the context of its importance to the development of high energy/high capacity lithium batteries. One of the issues raised in these studies is the fate of the Li2 MnO3 component as a function of voltage and repeated cycling. We have performed Raman spectroscopy based measurements that shed light on the transformations of the Li2 MnO3 phase as a function of state-of-charge. We find that on charging the Li2 MnO3 phase appears to de-lithiate at a rate at least equal to that of the LiMO2 phase, whereas, on discharge a Li2 MnO3 -like component reforms later in the discharge than does the LiMO2 phase. The absence of X-ray diffraction evidence for the presence of Li2 MnO3 after the first charge/discharge cycle can be reconciled by the possibility that the C2/m structured Li2 MnO3 exists in domains thick enough to diffract; but during subsequent discharging, a perturbed C2/m phase forms in conjunction with the re-lithiated LiMO2 phase in thin sheets (electrochemically induced topotaxy) that are not thick enough to diffract but form in sufficient volume to give Raman scattering similar to that of Li2 MnO3 .